Efektivitas Bantuan Hukum Untuk Menjamin Akses Terhadap Hukum Dan Keadilan - Sahabat, Andi Nazir; Arti, Asdar; Insani, Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Law No. 16 of 2011 concerning Legal Aid stipulates legal protection for citizens (access to justice) and equal rights for all citizens before the law (equality before the law), especially for the poor people of Gorontalo city. In Gorontalo City there are still people who have contact with the law who have not received the right to assist in investigations based on Law No. 16 Legal Aid of 2011 and Article 56 of the Criminal Procedure Code. Therefore, the current research addresses this issue, namely. problems in the implementation of legal aid to poor people who stumbled on criminal acts. The purpose of this study is to examine the problems of implementing legal aid for poor people who stumble on criminal cases. This study used an empirical approach, data collection techniques by interviewing respondents in this case, researchers, legal advisors, poor people who intersect with the law, and direct observation of the Criminal Investigation Unit of the Gorontalo City Police. The criminal police is a place where basic information is collected and then evaluated descriptively. The results of this study indicate that the legal assistance provided by the Gorontalo City Police is not very effective or maximal in helping the poor in mentoring and there are few human resources who work with the Gorontalo Police to help, so that the implementation of the provision of legal aid is not very effective.